2022
DOI: 10.3390/nu14235072
|View full text |Cite
|
Sign up to set email alerts
|

Quality Specific Associations of Carbohydrate Consumption and Frailty Index

Abstract: Background: The quality of carbohydrate consumed may influence the risk of frailty. In this study, we tested the hypothesis that indices of carbohydrate intake are associated with trajectories of frailty in participants of the Baltimore Longitudinal Study of Aging (BLSA). Methods: Cross sectional and longitudinal analyses were conducted in 1024 BLSA participants to examine the association between usual intake of carbohydrate and frailty index. Seven measures of carbohydrate consumption were estimated using dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…44 Moreover, a diet rich in fibre, exemplified by nuts, has been reported to decelerate the progression of ageing frailty, as evidenced in the Baltimore Longitudinal Study of Aging. 45 Also, high concentrations of urinary total polyphenols were found in relation with lower prevalence of frailty and prefrailty within a geriatric population. This leads to the deduction that a diet abundant in polyphenols, typified by foods such as nuts, may serve as a robust safeguard against the emergence of frailty.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…44 Moreover, a diet rich in fibre, exemplified by nuts, has been reported to decelerate the progression of ageing frailty, as evidenced in the Baltimore Longitudinal Study of Aging. 45 Also, high concentrations of urinary total polyphenols were found in relation with lower prevalence of frailty and prefrailty within a geriatric population. This leads to the deduction that a diet abundant in polyphenols, typified by foods such as nuts, may serve as a robust safeguard against the emergence of frailty.…”
Section: Discussionmentioning
confidence: 88%
“…And a cross‐sectional study involving 18,278 participants found that increasing omega‐3 polyunsaturated fatty acids, which are derived mainly from walnuts, particularly α‐linolenic acid, can effectively prevent low grip strength 44 . Moreover, a diet rich in fibre, exemplified by nuts, has been reported to decelerate the progression of ageing frailty, as evidenced in the Baltimore Longitudinal Study of Aging 45 . Also, high concentrations of urinary total polyphenols were found in relation with lower prevalence of frailty and prefrailty within a geriatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that high carbohydrate intake was associated with frailty, elevated inflammatory responses in the skeletal muscle, 25,26 and chronic low levels of inflammation that contribute to sarcopenia 27 . Frailty has been reported to be associated with higher oxidative stress and lower antioxidant markers in the body 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Mediterranean diet was protective in maintaining a lower FI [ 12 ]; three dietary patterns summarized based on Japanese older adults, including salt and pickles, sugar and a fat- and protein-rich dietary pattern, were associated with FI [ 13 ]; the results from Chinese older adults also found that the egg–bean–pickle–sugar pattern and fruit–vegetable–meat–fish pattern reduced frailty incidence [ 14 ]. A recent study demonstrated that dietary carbohydrates were positively associated with increased frailty risk in Baltimore participants [ 15 ]; thus, lower carbohydrate consumption may prevent frailty. The low-carbohydrate diet (LCD) score, with lower daily carbohydrate and higher protein and fat intake, has been associated with mortality [ 16 ], diabetes [ 17 ], cognition in the elderly [ 18 ] and weight loss [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, frailty was described using the frailty phenotype, which focuses on five physical factors, including unintentional weight loss, self-reported exhaustion, weakness (grip strength), slow walking speed and low physical activity, and not FI, which emphasizes accumulated health deficits [ 20 ]. Although low carbohydrate intake has been suggested as a frailty prevention strategy, currently relevant studies are limited to certain Western countries, such as the US [ 15 ] and France [ 20 ]. The results regarding the association of the LCD score with frailty risk are still considerably lacking in the Chinese context.…”
Section: Introductionmentioning
confidence: 99%